ABC of urology - Nethercliffe, Janine M. (ABC series, 2012)
"This new edition is needed to provide junior doctors and GPs with a comprehensive overview of urology focusing on the diagnosis and management of the most common urological conditions. Urology as a specialty is undergoing continuing technological and scientific innovation and there have been many recent changes to urology practice in favour of less invasive methods over surgeries. This edition will include the new techniques and procedures that have been developed since 2006 that allow for safer and more effective treatment"--Provided by publisher